Regulation of Endothelial and Vascular Functions by Carbon Monoxide via Crosstalk With Nitric Oxide - Choi, Yoon Kyung; Kim, Young-Myeong (Frontiers in Cardiovascular Medicine, 2021)
Carbon monoxide (CO), generated by heme oxygenase (HO), has been considered a signaling molecule in both the cardiovascular and central nervous systems. The biological function of the HO/CO axis is mostly related to other gaseous molecules, including nitric oxide (NO), which is synthesized by nitric oxide synthase (NOS). Healthy blood vessels are essential for the maintenance of tissue homeostasis and whole-body metabolism; however, decreased or impaired vascular function is a high-risk factor of cardiovascular and neuronal diseases. Accumulating evidence supports that the interplay between CO and NO plays a crucial role in vascular homeostasis and regeneration by improving endothelial function. Moreover, endothelial cells communicate with neighboring cells, such as smooth muscle cells, immune cells, pericytes, and astrocytes in the periphery and neuronal vascular systems. Endogenous CO could mediate the cell-cell communication and improve the physiological functions of the cardiovascular and neurovascular systems via crosstalk with NO. Thus, a forward, positive feedback circuit between HO/CO and NOS/NO pathways can maintain cardiovascular and neurovascular homeostasis and prevent various human diseases. We discussed the crucial role of CO-NO crosstalk in the cardiovascular and neurovascular systems.